SLR and GNSS test field for global geodetic network assessment in Riga - Kaminskis, Janis; Sulakova, Lubova; Salmins, Kalvis; Kaulins, Janis; Goldbergs, Lauris (International Conference “Environmental Engineering”, 2020)
The basic aim is to contribute to the world geodetic space in line with today’s scientific achievements. Riga geodynamic site is a thankful place for this, as it has long-term SLR observations and the longest GNSS records in Latvia. The goal is establishment of regional long-term geodetic monitoring station at LU Institute of Astronomy, Riga, Kandavas street 2, by joining at least two space geodetic technologies – the already installed laser-telescope LS-105 and GNSS − collocated, but not sufficiently linked. The capability of geodetic GNSS observations would uniquely complement Riga GNSS station and allow to determine more accurate coordinates of the LS-105 laser telescope and the long-term changes needed to accurately measure the positions of Earth satellites and other similar space objects. GNSS Observation Station will contribute to the development of positioning and position long-term change to accuracy of less than 1mm, one of the current global goals of GGOS. We plan to solve the problem with the exact position of the telescope LS-105 it will contribute to the development of scientific research and applied potential of the LU Satellite Laser Ranging station. From the national point of view geodetic station serves as an important point for Latvian National Geodetic Network, long term large infrastructure planning, engineering communications, cartography, etc. From a global perspective the station will be one of very few such stations in the region and the only one in the Baltics capable of valuable contribution to ITRF network. Preparatory work for the study has started by selecting and consolidating geodetic points for further measurements.
Keywords: geodesy; satellite laser ranging; laser telescope; data processing; collocated techniques